Gender transformation in the academy - Berheide, Catherine White; Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Bingley, U.K. : Emerald, 2014)
Gender inequality/inequity in the academy has been evidenced globally as women outnumber men seeking degrees in institutions of higher education, but remain concentrated in the lower faculty ranks and absent from administrative positions, particularly in the science, technology, engineering and mathematics (STEM) disciplines The chapters in this volume document the gender inequality in higher education in the United States as well as in Australia, Austria, Portugal, South Africa, and Sweden. They explore the reasons for it and test or suggest remedies. Several are based on projects funded by the U.S. National Science Foundation (NSF), which seeks to address the issue as it is evidenced in STEM disciplines through ADVANCE, a program developed to increase the participation and advancement of women in these disciplines. The authors consider womens situation in the context of a variety of types of educational settings including community colleges, primarily undergraduate institutions, and research-intensive universities.
Gender transformation in the academy : an introduction / Marcia Texler Segal, Vasilikie Demos -- The new STEM faculty profile : balancing family and dual careers / Patricia Wonch Hill, Mary Anne Homes, Julia McQuillan -- Carving a "third path" : faculty parents' resistance to the ideal academic worker norm / Marjukka Ollilainen, Catherine Richards Solomon -- Community colleges and the reproduction of gender in the academy : experiences of women STEM faculty / Cynthia D. Anderson ... [et al.] -- Strategies of academic parents to manage work-life conflict in research abroad / Amy Lubitow, Kathrin Zippel -- Achievement relative to opportunity : career hijacks in the academy / Beverley Hill, Judith Secker, Fay Davidson -- Emerging gender parity and persistent differences : cultural shifts among faculty cohorts at a primarily undergraduate institution / Elizabeth Borland, Diane C. Bates -- Department Chairs' perspectives on work, family, and gender : pathways for transformation / Amy S. Wharton, Mychel Estevez -- Gendered networks : professional connections of science and engineering faculty / Deborah Belle, Laurel Smith-Doerr, Lauren M. O'Brien -- Processes and pathways : exploring promotion to full professor at two liberal arts colleges in the United States / Catherine White Berheide, Susan Walzer -- Advancement of mid-career faculty members : perceptions, experiences, and challenges / Maxwell Awando ... [et al.] -- Senior compared to junior women academic scientists : similar or different needs? / Sue V. Rosser -- Disproportionate awards for women in disciplinary societies / Erin L. Cadwalader, Joan M. Herbers, Alice B. Popejoy -- Minimizing the influence of gender bias on the faculty search process / Eve Fine ... [et al.] -- Gender bias in appointment procedures for full professors : challenges to changing traditional and seemingly gender neutral practices / Angela Wroblewski -- Women in higher education in South Africa / Dianne Shober -- Organizational change and gender equity in academia : using dialogical change to promote positive departmental climates / Melissa Latimer ... [et al.] -- Critical mass or incremental change? The effects of faculty gender composition in STEM / Amy Hillard ... [et al.] -- Women in academic leadership / Maria de Lourdes Machado Taylor, Kate White -- "Someone needs to be first" : women pioneers as change agents in higher education management / Helen Peterson.
Print version record
Keywords: Social Science -- Gender Studies; Gender studies, gender groups; Gender studies: women; Gender studies: men; Sex discrimination in higher education; Women college teachers -- Social conditions